The Relationship Between Sexually Transmitted Infections in Pregnant Women and the Incidence of Low Birth Weight (LBW) - Ningsi Baizurah; Anik Sri Purwanti (Journal of Educational Innovation and Public Health, 2025)
Background: Sexually transmitted infections (STIs) during pregnancy are a significant public health concern because they can adversely affect maternal and fetal health. STIs such chlamydia, gonorrhea, and syphilis can cause complications including preterm labor, intrauterine growth restriction, and increased risk of low birth weight (LBW) in newborns (Sari, 2020). LBW is defined a birth weight of less than 2,500 grams and is associated with higher infant morbidity and mortality (Nurhidayah, 2021). Despite public health efforts, STIs remain prevalent in reproductive-aged women, and their relationship with LBW requires further investigation in local healthcare settings. Objective: This study aimed to determine the relationship between sexually transmitted infections in pregnant women and the incidence low birth weight newborns. Methods: A quantitative, observational study with a cross-sectional design was conducted. Results: The results indicated a significant relationship between the presence of sexually transmitted infections in pregnant women and the occurrence of low birth weight in newborns. Among the 30 participants, mothers with STIs showed a higher incidence of LBW (p = 0.000), indicating statistically significant association. These findings suggest that STIs in pregnancy can adversely affect fetal growth and contribute to neonatal health risks. Conclusion: Sexually transmitted infections in pregnant women are significantly associated with the incidence of low birth weight in newborns. Screening, early detection, and appropriate management of STIs during pregnancy are crucial strategies reduce the risk of LBW and improve neonatal outcomes. Healthcare providers should integrate STI prevention and treatment programs into routine antenatal care to promote maternal and infant health.